Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.

Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Incorporation of dose-rate effects into the BIANCA biophysical model and application for space radiation risk assessment - E.I. Canay; M. Carante; A. Casali; E. Bernardini; D. Dondi; Dhanalakshmi Vadivel; L. Cansolino; E. Delgrosso; C. Ferrari; M. Pullia; F. Bonforte; J. Riback; et al. (Life Sciences in Space Research, 2026)

Covalently bound Eosin Y on chitosan as a removable photosensitizer for ranitidine degradation - Julieta L. Sacchetto; Alberto M. Barrera Llorente; Marcela Kuhn Beldomenico; José Natera; María J. Gramaglia; Gabriela Porcal; Silvana Plem; Gabriela V. Ferrari; Walter A. Massad (Chemosphere, 2026)

Geospatial heterogeneity of hotspots for incidence and late-stage diagnosis of breast, colorectal, and lung cancer - Andrew P. Loehrer; Heather A. Carlos; Julia E. Weiss; Qianfei Wang; Chelsea V. Leversedge; Julia E. Katter; Joseph D. Phillips; Dana Ferrari-Light; Tracy Onega; Xun Shi (Cancer Causes & Control, 2026)
Purpose Cancer control relies on the identification of populations at risk (hotspots) of new or late-stage cancer diagnoses. However, the extent to which hotspots differ between cancer sites or between outcome measures has been poorly characterized. We sought to determine the geospatial heterogeneity of hotspots of breast, colorectal, and lung cancer incidence and late-stage diagnoses. Methods We identified adult patients diagnosed with female breast, colorectal, and lung cancer between 2010 and 2019 in Indiana. To identify hotspots for incidence and late-stage diagnoses, we disaggregated the patient residential location information from the Census block group level to the approximated individual point level. Statistically significant hotspots were identified with kernel ratio estimation. The total areas of hotspots and the overlap between hotspots were compared. Results 133,773 patients diagnosed with breast (n = 54,903), colorectal (n = 28,594), and lung (n = 50,276) cancer were included. Geospatial visualization demonstrated marked spatial deviation, with little overlapping area between incidence and late-stage hotspots for all three cancer sites (1–266 km 2 ). However, there was slightly greater overlap in late-stage hotspots between the different cancer sites, with total overlapping hotspot areas ranging from 24 to 516 km 2 . Conclusions Our results demonstrate considerable geospatial heterogeneity of hotspots between different outcome measures and different sites of cancer. The use of disaggregated spatial data enables a more granular, precise comparison of cancer hotspots. The greatest overlap was seen between incidence hotspots of breast and colorectal cancer, which suggests similar spatial drivers and the potential for coordinated cancer control strategies.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Novel antimicrobial and antiangiogenic properties from riparin-type benzamides: synthesis, biological evaluation, and docking analysis - Gabriela R. de Sousa; Janaracy L. da Costa Marinho; Pedro Thiago R. de Figueiredo; João Pedro A. Torres; Laísa V. Cordeiro; Luciana Scotti; Edeltrudes O. Lima; Bruna Braga Dantas; Fillipe de Oliveira Pereira; Jailton De Souza-Ferrari; José Maria Barbosa-Filho (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Assessment of wildfire-induced hydrological changes in the south andes mountains of chile - G. Alejandra Stehr; V. Nicole Vyhmeister; C. Efraín Duarte; Francisco Nájera-De Ferrari; Vicente Saenger; Felipe Aburto; Rafael Rubilar; Carolina Merino-Guzmán; B. Francisco Matus (Journal of Hydrology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Swelling of Na-montmorillonite in the presence of dissolved gas molecules - Jerry Peprah Owusu; Konstantinos Karalis; Nikolaos I. Prasianakis; Alessio Ferrari; Sergey V. Churakov (Applied Clay Science, 2026)

Sustainable digitalisation - a system thinking approach for determining costs and benefits in the agri-sector - K. Soma; G. Brunori; C. Giagnocavo; F. Meulman; M. Ryan; R.M. Heredia Hortigüela; C. Iliopoulos; M. Paulus; A. Ferrari; E. Kilis; S. Grando; V. Bellon-Maurel; et al. (Agricultural Systems, 2026)

Pelagia noctiluca as a new model organism in marine ecotoxicology: effects of common surfactants - V. Ferrari; D. Prevedelli; E. Bergami (Chemosphere, 2025)

Fibroblast Activation Protein (FAP) as a possible therapeutic target in selected canine malignant tumours - S. Dell'Aere; D. Stefanello; E. Gariboldi; A. Ubiali; R. Ferrari; L. Auletta; M. Bocci; A. Galbiati; S. Cazzamalli; E. Gilardoni; V. Balbi; G. Bianchi; et al. (Journal of Comparative Pathology, 2025)

Platelet-derived growth factor receptor beta expression in primary and metastatic canine anal sac adenocarcinoma as a potential therapeutic target - A. Verdi; S. Dell'Aere; C. Zamboni; D. Stefanello; R. Ferrari; E. Gariboldi; L. Maniscalco; S. Iussich; C. Romanello; V. Grieco; C. Giudice; C. Recordati; et al. (Journal of Comparative Pathology, 2025)

Analysis of tight junction protein dynamics by immunohistochemistry in porcine intestinal epithelial cells (IPEC-J2) cells exposed to osmotic stress - B. Passeri; P. Borghetti; M. Andrani; M. Di Pentima; A. Luppi; E. De Angelis; V. Cavalli; L. Ferrari; R. Saleri (Journal of Comparative Pathology, 2025)

A reassessment of the history of the temporal resolution of rainfall data at the global scale - Renato Morbidelli; Alessia Flammini; Odinakachukwu Echeta; Raffaele Albano; Gabriel Anzolin; David Zumr; Wafae Badi; Nicola Berni; Miriam Bertola; José María Bodoque; Theo Brandsma; Arianna Cauteruccio; et al. (Journal of Hydrology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Cytogenetic analysis of meiotic behaviour and stability in a trigeneric hybrid (triticale x trigopiro) - M. Fradkin; E. J. Greizerstein; E. Grassi; V. Ferreira; M. R. Ferrari; L. Poggio (Protoplasma, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A method to predict space radiation biological effectiveness for non-cancer effects following intense Solar Particle Events - R.L. Ramos; M.P. Carante; E. Bernardini; A. Ferrari; P. Sala; V. Vercesi; F. Ballarini (Life Sciences in Space Research, 2024)

In vitro digestibility of rice and tapioca starch-based hydrogels produced by high-pressure processing (HPP) - Serena Carpentieri; Dominique Larrea-Wachtendorff; Gustavo V. Barbosa-Cánovas; Giovanna Ferrari (Innovative Food Science & Emerging Technologies, 2024)

Photosensitized oxygenation reactions as an alternative towards the degradation of fenamates and related pollutants using visible light - Eduardo L. Gutiérrez; Julieta Sacchetto; Francisco Boscá; M. Luisa Marín; Walter Massad; M. Paulina Montaña; Sandra Miskoski; Gabriela V. Ferrari (Journal of Water Process Engineering, 2024)

Influence of Weather Conditions on Sleeping Patterns and Selection of Foliage Cover of Sleeping Trees in Black-and-Gold, Howler Monkeys (Alouatta caraya) in Northern Argentina - Melina V. Brividoro; Luciana I. Oklander; Verónica I. Cantarelli; Marina F. Ponzio; Héctor R. Ferrari; Martín M. Kowalewski (International Journal of Primatology, 2023)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Hybrid multi-core shell magnetic nanoparticles for wet peroxide oxidation of paracetamol: Application in synthetic and real matrices - Adriano S. Silva; Fernanda F. Roman; Arnaldo V. Dias; Jose L. Diaz de Tuesta; Alexandre Narcizo; Ana Paula F. da Silva; Ihsan Çaha; Francis Leonard Deepak; Manuel Bañobre-López; Ana M.C. Ferrari; Helder T. Gomes (Journal of Environmental Chemical Engineering, 2023)

Shear strength and shear stiffness analysis of compacted Wyoming-type bentonite - X. Pintado; S. Kumpulainen; E. Romero; A. Lloret; R.C. Weber; A. Ferrari; M.V. Villar; A. Abed; W. Solowski; V. Heino (Geomechanics for Energy and the Environment, 2023)

Non-toxic acid-free glyoxal fixative for veterinary histopathology, immunohistochemistry and molecular analysis - V. Zappulli; F. Torrigiani; P. Detillo; S. Iussich; M. Rondena; C. Gola; L. MInoli; E. Morello; E.I. Ferraris; A. Rigillo; B. Bussolati (Journal of Comparative Pathology, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

A review of the main methods for composite adsorbents characterization - Mateus T. Nazari; Carlos Schnorr; Cesar V. T. Rigueto; Ingridy Alessandretti; Flávia Melara; Nathália F. da Silva; Larissa Crestani; Valdecir Ferrari; Julien Vieillard; Guilherme L. Dotto; Luis F. O. Silva; Jeferson S. Piccin (Environmental Science and Pollution Research, 2022)

Long-term use of pharmacological treatment in Alzheimer’s disease: a retrospective cohort study in real-world clinical practice - G Lombardi; N Lombardi; A Bettiol; G Crescioli; C Ferrari; G Lucidi; C Polito; V Berti; V Bessi; S Bagnoli; B Nacmias; A Vannacci; et al. (European Journal of Clinical Pharmacology, 2022)

Effects of Magnetite Nanoparticles and Static Magnetic Field on Neural Differentiation of Pluripotent Stem Cells - Ana T. Semeano; Fabiano A. Tofoli; Juliana C. Corrêa-Velloso; Ana P. de Jesus Santos; Ágatha Oliveira-Giacomelli; Rafaela R. Cardoso; Mateus A. Pessoa; Edroaldo Lummertz da Rocha; Gustavo Ribeiro; Merari F. R. Ferrari; Lygia V. Pereira; Yang D. Teng; et al. (Stem Cell Reviews and Reports, 2022)

Sensitivity Analysis of Single Beat Left Ventricular Elastance Estimation by Chen Method - A. Di Molfetta; G. Ferrari; V. Cusimano; G. Di Ruzza; P. Mollo; D. Boncompagni; M. Cesario; C. Volponi; M. Massetti; M. Menichelli (Cardiovascular Engineering and Technology, 2022)

The Effects of Social Factors and Kinship on Co-sleeping of Black-and-Gold Howler Monkeys (Alouatta caraya) - Melina V. Brividoro; Luciana I. Oklander; Verónica I. Cantarelli; Marina F. Ponzio; Héctor R. Ferrari; Martin M. Kowalewski (International Journal of Primatology, 2021)

The predictive capacity of the high resolution weather research and forecasting model: a year-long verification over Italy - L. Apicella; S. Puca; M. Lagasio; A. N. Meroni; M. Milelli; N. Vela; V. Garbero; L. Ferraris; A. Parodi (Bulletin of Atmospheric Science and Technology, 2021)
Numerical models are operationally used for weather forecasting activities to reduce the risks of several hydro-meteorological disasters. The overarching goal of this work is to evaluate the Weather Research and Forecasting (WRF) model predictive capabilities over the Italian national territory in the year 2018, in two specific cloud resolving configurations. The validation is carried out with a fuzzy logic approach, by comparing the precipitation predicted by the WRF model, and the precipitation observed by the national network. The fuzzy logic technique, by considering different intensity thresholds, allows to identify the reliable spatial scales of the forecasts. The same approach is applied to evaluate the performances of COSMO-2I model, a state-of-the-art numerical model configuration used for operational activities. For the entire year, except for summer, the model predictive capabilities are high, with useful forecasts for structures of medium intensities down to O (10 km) length scales. In summer the skills decrease mainly because of localization errors. The work aims to provide a robust evaluation of the forecast performances of another convection permitting operational meteorological models currently available in Italy.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Stereotactic radiation therapy in oligometastatic colorectal cancer: outcome of 102 patients and 150 lesions - V. Dell’Acqua; A. Surgo; F. Kraja; J. Kobiela; Maria Alessia Zerella; P. Spychalski; S. Gandini; C. M. Francia; D. Ciardo; C. Fodor; A. M. Ferrari; G. Piperno; et al. (Clinical & Experimental Metastasis, 2019)

Diallelic Analysis of Endogamic Maize Lines with Emphasis on Agronomic Traits of Tassel in Different Environments - D. Barreta; M. Nardino; V. A. Konflanz; A. J. de Pelegrin; M. Ferrari; V. J. Szareski; I. R. Carvalho; V. Q. de Souza; A. C. de Oliveira; L. C. da Maia (Journal of Crop Science and Biotechnology, 2019)

Chronic Hippocampal Expression of Notch Intracellular Domain Induces Vascular Thickening, Reduces Glucose Availability, and Exacerbates Spatial Memory Deficits in a Rat Model of Early Alzheimer - Pablo Galeano; María C. Leal; Carina C. Ferrari; María C. Dalmasso; Pamela V. Martino Adami; María I. Farías; Juan C. Casabona; Mariana Puntel; Sonia Do Carmo; Clara Smal; Martín Arán; Eduardo M. Castaño; et al. (Molecular Neurobiology, 2018)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Impairment of mitochondria dynamics by human A53T α-synuclein and rescue by NAP (davunetide) in a cell model for Parkinson’s disease - T. Q. Melo; K. C. van Zomeren; M. F. R. Ferrari; H. W. G. M. Boddeke; J. C. V. M. Copray (Experimental Brain Research, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Geological connectivity drives microbial community structure and connectivity in polar, terrestrial ecosystems - Belinda C. Ferrari; Andrew Bissett; Ian Snape; Josie van Dorst; Anne S. Palmer; Mukan Ji; Steven D. Siciliano; Jonathon S. Stark; Tristrom Winsley; Mark V. Brown (Environmental Microbiology, 2016)
Summary Landscape heterogeneity impacts community assembly in animals and plants, but it is not clear if this ecological concept extends to microbes. To examine this question, we chose to investigate polar soil environments from the Antarctic and Arctic, where microbes often form the major component of biomass. We examined soil environments that ranged in connectivity from relatively well‐connected slopes to patchy, fragmented landforms that comprised isolated frost boils. We found landscape connectedness to have a significant correlation with microbial community structure and connectivity, as measured by co‐occurrence networks. Soils from within fragmented landforms appeared to exhibit less local environmental heterogeneity, harboured more similar communities, but fewer biological associations than connected landforms. This effect was observed at both poles, despite the geographical distances and ecological differences between them. We suggest that microbial communities inhabiting well‐connected landscape elements respond consistently to regional‐scale gradients in biotic and edaphic factors. Conversely, the repeated freeze thaw cycles that characterize fragmented landscapes create barriers within the landscape and act to homogenize the soil environment within individual frost boils and consequently the microbial communities. We propose that lower microbial connectivity in the fragmented landforms is a function of smaller patch size and continual disturbances following soil mixing.

Microbial diversity at Mitchell Peninsula, Eastern Antarctica: a potential biodiversity “hotspot” - Mukan Ji; Josie van Dorst; Andrew Bissett; Mark V. Brown; Anne S. Palmer; Ian Snape; Steven D. Siciliano; Belinda C. Ferrari (Polar Biology, 2016)

Bronchial microbiome of severe COPD patients colonised by Pseudomonas aeruginosa - L. Millares; R. Ferrari; M. Gallego; M. Garcia-Nuñez; V. Pérez-Brocal; M. Espasa; X. Pomares; C. Monton; A. Moya; E. Monsó (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Spatial models to support the management of coastal marine ecosystems: a short review of the best practices in Liguria, Italy - M. VACCHI; M. MONTEFALCONE; V. PARRAVICINI; A. ROVERE; P. VASSALLO; M. FERRARI; C. MORRI; C. N. BIANCHI (Mediterranean Marine Science, 2013)
Spatial modelling is an emerging approach to the management of coastal marine habitats, as it helps understanding and predicting the results of global change. This paper reviews critically two recent examples developed in Liguria, an administrative region of NW Italy. The first example, aiming at predicting habitat status depending on pressures, provides managers with the opportunity of envisaging different scenarios for the consequences of coastal development choices. The second example defines the status of an important Mediterranean coastal marine habitat (Posidonia oceanica meadows) under natural conditions, allowing for quantifying human impacts on regressed meadows. Both modelling approaches are useful to define the targets of coastal management, and may help choosing the best management option. Well-planned and sustained monitoring is essential to model validation and improvement.

Anti N1 Cross-Protecting Antibodies Against H5N1 Detected in H1N1 Infected People - E. Frobert; M. Bouscambert-Duchamp; V. Escuret; S. Mundweiler; M. Barthélémy; F. Morfin; M. Valette; C. Gerdil; B. Lina; O. Ferraris (Current Microbiology, 2010)

Abnormal meiosis in tetraploid genotypes ofBrachiaria brizantha (Poaceae) induced by colchicine: its implications for breeding - A. B. Mendes-Bonato; M. Ferrari Felismino; A. M. Souza Kaneshima; C. Pessim; V. Calisto; M. Suely Pagliarini; C. Borges do Valle (Journal of Applied Genetics, 2009)

Establishing physiological blood parameters in the loggerhead sea turtle (Caretta caretta) - D. Gelli; V. Ferrari; A. Zanella; P. Arena; L. Pozzi; S. Nannarelli; C. Vaccaro; D. Bernardini; S. Romagnoli (European Journal of Wildlife Research, 2009)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Meat intake and bladder cancer in a prospective study: a role for heterocyclic aromatic amines? - B. Lumbreras; S. Garte; K. Overvad; A. Tjonneland; F. Clavel-Chapelon; J. P. Linseisen; H. Boeing; A. Trichopoulou; D. Palli; M. Peluso; V. Krogh; R. Tumino; et al. (Cancer Causes & Control, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effect of Weaning and Vaccinations on Immune and Hormonal Parameters in Neonatal Piglets - P. Borghetti; L. Ferrari; V. Cavalli; E. De Angelis; R. Saleri; A. Corradi; P. Martelli (Veterinary Research Communications, 2006)

Bone Mineral Density in Two Boxer Dogs Affected by Moderate to End-stage Chronic Renal Failure - A. Zotti; M. Caldin; E. Vettorato; V. Ferrari; L. Cavicchioli; D. Bernardini (Veterinary Research Communications, 2006)

Dinuclear platinum complexes with N,N′-bis(aminoalkyl)-1,4-diaminoanthraquinones as linking ligands. Part I. Synthesis, cytotoxicity, and cellular studies in A2780 human ovarian carcinoma cells - Bart A. J. Jansen; Peter Wielaard; Ganna V. Kalayda; Maura Ferrari; Chris Molenaar; Hans J. Tanke; Jaap Brouwer; Jan Reedijk (JBIC Journal of Biological Inorganic Chemistry, 2004)

Calf and shin muscle oxygenation patterns and femoral artery blood flow during dynamic plantar flexion exercise in humans - S. Shimizu; F. Chiarotti; M. Ferrari; A. Kagaya; V. Quaresima; S. Homma; K. Azuma (European Journal of Applied Physiology, 2001)

Synchrotron powder diffraction study of phengite 3T from the Dora-Maira massif: P - V - T equation of state and petrological consequences - A. Pavese; G. Ferraris; V. Pischedda; M. Mezouar (Physics and Chemistry of Minerals, 1999)

Distribution of microbial assemblages in the Central Arctic Ocean Basin studied by PCR/DGGE: analysis of a large data set - V. C. Ferrari; J. T. Hollibaugh (Hydrobiologia, 1999)

Isolation and characterization of cytopathic strains of rotavirus from rabbits - G. Castrucci; M. Ferrari; F. Frigeri; V. Cilli; L. Perucca; G. Donelli (Archives of Virology, 1985)

Reactivation in calves ofBovid herpesvirus 2 latent infection - G. Castrucci; M. Ferrari; F. Frigeri; S. Ranucci; V. Cilli; B. Tesei; L. Rampichini (Archives of Virology, 1982)